Visit to Howard Hughes' Spruce Goose Exhibit in Long Beach - Watkins, Howard::::::::: (1984)
Display sign re: Wright Brothers Model B Aircraft-1911 Exact reproduction of Wright Brothers plane that flew at Kitty Hawk, NC